Multiculturalism, liberalism, and democracy - Bhargava, Rajeev; Bagchi, Amiya Kumar; Sudarshan, R., 1953- (New Delhi ; New York : Oxford, 1999)
Papers originally presented at a seminar organized by the Centre for Studies in Social Sciences, Calcutta.
Keywords: Multiculturalism -- India; Liberalism -- India; Democracy -- India